Microplastics in sea surface waters in the Southern Bight of the North Sea - Hoehn, Danja P.; McGoran, Alexandra R.; Barry, Jon; Russell, Josie; Nicolaus, E. E. Manuel; Bakir, Adil (Frontiers in Marine Science, 2024)
Microplastic pollution in the marine environment is of concern, with evidence of harmful effects on marine biota and ecosystems. There is still a knowledge gap of the mass of plastics supplied to the ocean and plastics observed in the ocean, indicating a missing sink. Therefore, baseline and monitoring data are needed to inform policy and regulatory measures. The goal of this study was to collect harmonised data of microplastics from the surface of the ocean using the Neuston Microplastic Catamaran. This study shows that the surface water of the coastal ocean in the North Sea holds/sustains high concentrations of microplastic, which exceed previously recorded measurements from the North-East Atlantic and Scottish Waters, indicating that the total stock of plastics might be much higher than previously determined. Microplastics were detected in all samples with concentrations ranging from 857 to 25,462 items km−2. The majority of microplastics analysed were fragments of polyethylene, polypropylene, and polystyrene in the size range of 1,000–5,000 µm. Mesoplastics (>5,000 µm) mainly in the form of filaments were found with concentrations ranging from 0 to 2,139 items km−2, and macroplastics (>5,000 µm) in the form of fragments and filaments were also found with concentrations ranging from 0 to 1,078 items km−2. These fragments and filaments likely originate from the break-up of common macrolitter items in the environment, such as plastic bags, bottles, and fishing gears, which are commonly comprised of similar polymers to those found in the present study. Our findings demonstrate that litters of all size classes are abundant in surface water, highlighting that it is a key compartment for the transport of marine litter and should be monitored to better our understanding of the fate and danger of plastic contamination in our ocean.